Detecting mobile producer’s position in a wireless named data network environment using signal strength - Ahmed, Muhammed Zaharadeen (Springer, 2022)
Named Data Networking (NDN) is a new Content Centric Network architecture that can possibly overwhelm most issues of IP mobility and security. The NDN is centered on addressing contents by themselves using names, rather than assigning IP addresses to packets on hosts where information is located on the global Internet. Due to the developing scope of remote access around the world and Wi-Fi accessibility, scenarios change because of additional networking devices. This paper analyses existing methodologies of mobile device communication using Wi-Fi in NDN. This involves using a mobile producer and a rendezvous node connected via content routers in an NDN scenario. Their location is detected and predicted immediately handoff occur and it send content transmission as a consumer. The approach of transmitting content signals uses sign power pointer (RSSI), TOA, and TSE in the network. Several challenges were noted and pointed out enhance future work.